Biologically oriented synthesis of medicines (BIODS) based on heterylpoxid 2,5- disubstituted 1,3,4-oxadiazoles (Part 1) - Yu. V. Karpenko; O. I. Panasenko; Ye. H. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
At the present stage of development of medical chemistry, many basic synthetic approaches to the synthesis of 1,3,4-oxadiazole structures are known, which are focused mainly on the principles of combinatorial chemistry with a wide range of biological activity.